ANALYSIS OF COMPUTER DESIGN PROGRAMS FOR SEWING ITEMS - Dadamirzayev Bahromjon Bakhtiyar ogli; Abdujalilova Mavludaxon Qoshaqboy qizi (Web of Journals Publishing, 2024)
This article discusses the advantages and disadvantages of computer-aided design programs for sewing products used in sewing enterprises.
Keywords: Adobe Illustrator, TUKA cad, CoreI DRAW, Gerber Accumark, Optitex, CLO3D